2014
DOI: 10.11604/pamj.2014.17.44.3399
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to antiepileptic drugs among children attending a tertiary health unit in a low resource setting

Abstract: IntroductionEpilepsy is one of the neglected and highly stigmatised diseases, yet it is very common affecting about 70 million people worldwide. In Uganda, the estimated prevalence of epilepsy is 13% with about 156 new cases per 100,000 people per year. Adherence to antiepileptic drugs is crucial in achieving seizure control yet in Uganda; there is lack of information on adherence to antiepileptic drugs and the factors that affect this among children. This study was therefore designed to determine the level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 26 publications
6
30
1
Order By: Relevance
“…A Ugandan study found that almost 80% of people reported being adherent to AED treatment, but only about a quarter were adherent when serum drug levels were checked [49]. Good adherence to AED is associated with better seizure control, improved job prospects, increased productivity, reduced road traffic accidents, and a better overall QOL [111].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Ugandan study found that almost 80% of people reported being adherent to AED treatment, but only about a quarter were adherent when serum drug levels were checked [49]. Good adherence to AED is associated with better seizure control, improved job prospects, increased productivity, reduced road traffic accidents, and a better overall QOL [111].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the programs (75%) target rural or suburban populations. Even where care was based in tertiary care centers, they also served rural and community outposts [45,49,59]. Some of the rural care programs recruited individuals for treatment following epidemiological surveys, community engagements or after recognizing particular needs.…”
Section: Characteristics Of the Publications Retrievedmentioning
confidence: 99%
“…10 Our findings are in fact similar to other adherence data based solely on self-report of the pediatric patient or parent. 11,12,32 …”
Section: Discussionmentioning
confidence: 99%
“…9 Previous studies have documented several factors affecting adherence to AEDs in children and adolescents, but these have been done in developed countries or in tertiary care hospital settings. 10,11 There are no local studies, which have investigated the problem of nonadherence among children with epilepsy in Pakistan. Therefore, investigating the magnitude of the problem and the factors associated with nonadherence is essential in designing an appropriate health education strategy and having a plan to reduce the impact of the problem.…”
Section: Introductionmentioning
confidence: 99%